Penguatan Literasi Bahasa Indonesia di Sekolah Dasar melalui Strategi Pembelajaran yang Mendorong Berpikir Kritis dan Kreatif - Erwin Eka Saputra; Kasmawati Kasmawati; Chairan Zibar L. Parisu (Prodi PGSD Unsultra, 2025)
Literacy skills are a fundamental foundation in primary education, encompassing not only reading and writing abilities but also critical and creative thinking skills. However, field observations show that many elementary school students still have low literacy levels, particularly in understanding texts and expressing ideas both in writing and speaking. This community service activity aimed to strengthen Indonesian language literacy in elementary schools through innovative learning strategies that encourage critical and creative thinking. The target of this program was elementary school teachers across Baruga Subdistrict, Kendari City, Southeast Sulawesi Province. The implementation methods included training sessions, mentoring, and evaluations of teaching strategies based on narrative, explanatory, and descriptive texts, combined with critical reading and creative writing techniques. The results of the program showed a significant increase in teachers’ understanding of comprehensive literacy concepts and their ability to design and apply learning models based on Higher Order Thinking Skills (HOTS). In addition, teachers were able to develop project-based learning activities and visual literacy strategies that enabled students to think logically, reflectively, and creatively. This program is expected to contribute significantly to improving the quality of Indonesian language learning at the elementary school level and to serve as a replicable model for other schools seeking to strengthen 21st-century literacy skills.